2022
DOI: 10.3390/en15113974
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Study on Microwave-Assisted Hydrothermal Liquefaction of Malaysian Macroalgae Chaetomorpha sp. for Phenolic-Rich Bio-Oil Production

Abstract: There are several methods of biomass conversion, including hydrothermal liquefaction (HTL). The implementation of microwave technology in the HTL process is still new, especially on the conversion of marine biomass into bio-crude. In this work, the macroalgae Chaetomorpha sp. was used as the biomass feedstock to produce phenolic-rich bio-oil through microwave-assisted HTL. Chaetomorpha sp. was abundantly found in Malaysia, creating a green tides issue. By utilizing these algae, the green tide issue can be solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 81 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…to biocrude. 523 The maximum biodiesel yield of 21.47 wt % and phenolic yield of 19.22 wt % was obtained at optimum operation conditions of 226 °C, 76 min, water-to-biomass ratio of 30:1, and with pressure of 42 bar. The sensitivity analysis showed that HTL process is mostly impacted by the water-tobiomass ratio because water is the main microwave absorber.…”
Section: Factors Influencing the Performance Of Microwave-assisted Hy...mentioning
confidence: 90%
See 4 more Smart Citations
“…to biocrude. 523 The maximum biodiesel yield of 21.47 wt % and phenolic yield of 19.22 wt % was obtained at optimum operation conditions of 226 °C, 76 min, water-to-biomass ratio of 30:1, and with pressure of 42 bar. The sensitivity analysis showed that HTL process is mostly impacted by the water-tobiomass ratio because water is the main microwave absorber.…”
Section: Factors Influencing the Performance Of Microwave-assisted Hy...mentioning
confidence: 90%
“…A recent study optimized microwave-assisted HTL (MW-HTL) process conditions (temperature 200–260 °C, holding time 30–90 min, water-to-microalgae biomass ratio 10–30, preloaded pressure 25–45 bar) to improve the yield for the conversion of marine microalgae ( Chaetomorpha sp.) to biocrude . The maximum biodiesel yield of 21.47 wt % and phenolic yield of 19.22 wt % was obtained at optimum operation conditions of 226 °C, 76 min, water-to-biomass ratio of 30:1, and with pressure of 42 bar.…”
Section: Coupling Of Hydrothermal Treatment With Other Technologiesmentioning
confidence: 94%
See 3 more Smart Citations